Establishing and Sustaining an ECPR Program - Laussen, Peter C.; Guerguerian, Anne-Marie (Frontiers in Pediatrics, 2018)
The use of extracorporeal support after failed return of a spontaneous ciruculation during cardiopulmonary resuscitation (ECPR) is well described. There are 4 distinct phases for resuscitation with ECPR and the time spent in each phase is critical for successful outcome. Recommendations for ECPR previously published by the American Heart Association provide the context for implementing a consistent and well-rehearsed system for ECPR, by people with the knowledge, experience and resources to deploy ECPR in the most optimal time frame possible in selected patient populations. In this manuscript we review the current status of ECPR for acute cardiac failure and the components we believe are necessary to develop and sustain a reliable and resilient program.